Orthodox Perspectives on the Church as an Evangelizing, Eucharistic Community: A Case Study of the Orthodox Parish of St John of Kronstadt, Bath, UK - Kolosova, Alison (Ecclesial Futures, 2024)
This article presents a case study of the Orthodox parish of St John of Kronstadt in Bath, UK, an Orthodox Christian lay community founded in 1980 in response to the inspiration of St John of Kronstadt and Fr Alexander Schmemann. Based on interviews with parishioners and the author’s own experience of the community, the article delineates the main features of the parish’s communal life of liturgical prayer, hospitality and witness in the wider community. The second part of the article explores the broader contribution of St John and Fr Alexander to the development of Orthodox ecclesial and missional understandings and practices in the contemporary world. It delineates the historical, ecclesial and theological contexts in which their teachings and practices originated and argues that amidst these contexts we can trace the origins of the Eucharistic ecclesiology and understandings of human personhood and community which have pervaded Orthodox theology in the twentieth and twenty-first centuries. These have laid the groundwork for the perspective that Christian mission and witness are a continuation of the Eucharistic community’s experience of the Kingdom of God, the ‘liturgy after the liturgy’. The article concludes with a plea for greater dialogue based on the common ground between Western missiological discourse on the nature of post-Christendom evangelism and the ecclesial experience of Orthodox diaspora communities.